Il linguaggio dei colori: intervista a Ruggero Savinio (Materiali di Estetica. Terza serie, 2023)
In June 2022, Ruggero Savinio, the son of Alberto Savinio and the nephew of Giorgio de Chirico, gave an interview to Gabriele Civello about the language of the colours.
Keywords: Colours; Language; Painting; Art